Why Tracking Theories Should Allow for Clean Cases of Reliable Misrepresentation - Mendelovici, Angela (2016)
Reliable misrepresentation is getting things wrong in the same way all the time. In Mendelovici 2013, I argue that tracking theories of mental representation cannot allow for certain kinds of reliable misrepresentation, and that this is a problem for those views. Artiga 2013 defends teleosemantics from this argument. He agrees with Mendelovici 2013 that teleosemantics cannot account for clean cases of reliable misrepresentation, but argues that this is not a problem for the view. This paper clarifies and improves the argument in Mendelovici 2013 and responds to Artiga’s arguments. Tracking theories, teleosemantics included, really do need to allow for clean cases of reliable misrepresentation.